Genetic diversity of Burkholderia contaminans isolates from cystic fibrosis patients in Argentina - Martina, Pablo Francisco (2013)
A total of 120 Burkholderia cepacia complex isolates collected during 2004-2010 from 66 patients in two cystic fibrosis reference centers in Argentina were analyzed. Burkholderia contaminans was the species most frequently recovered (57.6%), followed by Burkholderia cenocepacia (15%), a species distribution not reported so far. The recA-PCR-based techniques applied to the B. contaminans isolates revealed that 85% of the population carried the recA-ST-71 allele. Our results showed the utility of BOXPCR genotyping in analyzing B. contaminans diversity. This approach allowed us to address clonal transmission during an outbreak and the genetic changes occurring in infecting bacteria over the course of chronic infection.